Understanding Human Nature in the View of Islamic Educational Philosophy - Andi Achruh AB. Pasinringi; Kamal; Afifuddin; Nurchamidah (al-Afkar, Journal For Islamic Studies, 2023)
In essence, human beings are glorified creatures of Allah SWT, this glory can be obtained if humans place themselves as creatures before their God, human nature can be interpreted as a tendency to understand the essence that is fixed and does not change in human beings, as well as signifies its characteristics that distinguish it from humans. another. Human nature in philosophy is a tendency to assume that humans have a pre-existent definition of humanity that is able to clearly distinguish it from its existence. So essence is more important than existence. The essence of humanity in humans is attached at all times in humans from birth to death. Humans in actualizing their humanity in various lives will get respect. Human potential based on the Islamic view is a created form. So that with the creation of this human being, the Creator, namely Allah SWT, has provided potentials for life related to the concept of human nature (A. Aziz, 2013: Ta'allum: Journal of Islamic Education). Human nature is a gift from Allah SWT that is attached to humans so that humans have a noble position when compared to other creatures created by Allah SWT.